Hubungan Derajat Miopia dengan Tekanan Intraokuler pada Pasien di RS Mata Prima Vision Medan - Singh, Jak Mohan; Yumardika, Deza; Suandy , Suandy (Syntax Corporation, 2025)
Myopia is one of the most common refractive errors found in the community and has become a major cause of visual impairment and blindness worldwide. The degree of myopia may influence intraocular pressure (IOP), which is a major risk factor for glaucoma. This study aimed to determine the relationship between the degree of myopia and intraocular pressure among patients at Prima Vision Eye Hospital Medan. This research employed an analytical method with a cross-sectional design. The study sample consisted of 48 patients diagnosed with myopia who met the inclusion criteria. The degree of myopia was categorized based on refraction examination results, while IOP was measured using non-contact tonometry. Data were analyzed using the Chi-Square test. The results showed that most respondents were aged 21–30 years (39.6%) and the majority were female (58.3%). Most patients had moderate myopia (47.9%). Statistical analysis revealed a significant relationship between the degree of myopia and intraocular pressure (p < 0.05). In conclusion, there is a significant correlation between the degree of myopia and intraocular pressure among patients at Prima Vision Eye Hospital Medan. It is recommended that patients with high myopia undergo regular eye examinations for early detection of increased IOP and glaucoma risk.